Recovering international relations : the promise of sustainable critique - Levine, Daniel J. (Oxford : Oxford University Press, 2013)
Surveying six decades of scholarship, 'Recovering International Relations' suggests new ethical and methodological foundations for the study of world politics. IR is conceived as a vocation one that must balance the insights of normative and empirical theory against each other to address a densely populated heavily armed, and persistently diverse world.
Includes bibliographical references and index.
Description based on print version record.
Keywords: International relations -- Philosophy